ʺEthical Issues in the creation of an inclusive educational environment of a general secondary education institutionʺ - Grianyk, D. (Problems of Engineer-Pedagogical Education, 2024)
The article presents the results of a survey among pedagogical staff of general secondary educational institutions in Kharkiv to determine the current situation with the ethical component of the process to create an inclusive environment in a general secondary educational institution. A total of 160 teachers from Kharkiv lyceums No. 100 and No. 164 (Kyiv district), No. 65 and No. 127 (Novobavarskyi district) took part in the research. The results of the survey presented in this paper demonstrate that all respondents have a correct understanding the concept of "inclusive education," indicating that they are aware of a number of problems associated with this phenomenon. The paper identifies the areas and problems of organizing an inclusive environment and analyzes the features of each of them. These areas include the organization of interaction between children in an inclusive classroom, the organization of communication with students' parents, and ensuring communication between teachers in an inclusive classroom and other members of the psychological and pedagogical support team. Among the main problems arising in the inclusive environment of GSEIs, the vast majority of surveyed teachers identify the difficulty of individualizing learning, 98% emphasize the difficulty of ensuring the flexibility of the educational process, and 91% feel a lack of specific competence. It has been found that significant ethical correction is required in student-student interaction, according to 57% of respondents, and teacher-student interaction - 41% of respondents. Based on the results of the study, it was concluded that the level of tolerance development is not sufficient for both students and teachers. Today, 39% of respondents support the idea that children with SEN do not belong in educational institutions with normative students. The theoretical analysis presented in the article shows that the issue of the ethical component of the inclusive environment of the SES remains insufficiently studied in Ukrainianlanguage sources, which is a significant motivation for further research in this area. The research materials presented in the paper allow us to conclude that the current need is to develop methodological materials to develop ethical competence in modern teachers to work in an inclusive GSE environment and to meet the current needs of society in supporting sustainable development and implementing the idea of humanizing the educational environment.